login
A118058
a(n) = 49n^2 - 28n - 20.
3
1, 120, 337, 652, 1065, 1576, 2185, 2892, 3697, 4600, 5601, 6700, 7897, 9192, 10585, 12076, 13665, 15352, 17137, 19020, 21001, 23080, 25257, 27532, 29905, 32376, 34945, 37612, 40377, 43240, 46201, 49260, 52417, 55672, 59025, 62476, 66025
OFFSET
1,2
COMMENTS
In general, all sequences of equations which contain every positive integer in order exactly once (a pairwise equal summed, ordered partition of the positive integers) may be defined as follows: For all k, let x(k)=A001652(k) and z(k)=A001653(k). Then if we define a(n) to be (x(k)+z(k))n^2-(z(k)-1)n-x(k), the following equation is true: a(n)+(a(n)+1)+...+(a(n)+(x(k)+z(k))n+(2x(k)+z(k)-1)/2)=(a(n)+ (x(k)+z(k))n+(2x(k)+z(k)+1)/2)+...+(a(n)+2(x(k)+z(k))n+x(k)); a(n)+2(x(k)+z(k))n+x(k))=a(n+1)-1; e.g., in this sequence, x(2)=A001652(2) and z(2)=A001653(2)=29; cf. A000290,A118057,A118059-A118061.
FORMULA
a(n)+(a(n)+1)+...+(a(n)+98n+34)=7(7n-2)(7n+5)(14n+3)/2; e.g., 337+338+...+518=77805=7*19*26*45/2.
a(n) = 3*a(n-1)-3*a(n-2)+a(n-3). G.f.: x*(1+117*x-20*x^2)/(1-x)^3. - Colin Barker, Jun 30 2012
EXAMPLE
a(3)=49*3^2-28*3-20=337, a(4)=49*4^2-28*4-20=652 and 337+338+...+518=519+...+651.
MATHEMATICA
Table[49*n^2 - 28*n - 20, {n, 10}] (* Vincenzo Librandi, Jul 08 2012 *)
PROG
(Magma) [49*n^2-28*n-20: n in [1..50]]; // Vincenzo Librandi, Jul 08 2012
(PARI) a(n)=49*n^2-28*n-20 \\ Charles R Greathouse IV, Jun 17 2017
CROSSREFS
Sequence in context: A098114 A135805 A327912 * A269037 A144524 A052768
KEYWORD
nonn,easy
AUTHOR
Charlie Marion, Apr 26 2006
EXTENSIONS
Corrected by Franklin T. Adams-Watters and T. D. Noe, Oct 25 2006
STATUS
approved